Proceedings of the Thirteenth Conference on Applied Linguistics (CONAPLIN 2020) 2021
DOI: 10.2991/assehr.k.210427.084
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Teachers’ Voices of Learner Autonomy in EFL Online Learning Context

Abstract: Autonomy of English language learners in a technology-supported learning environment has attracted much academic interest. However, learner autonomy in the Indonesian EFL setting has not commonly been considered as an important teaching and learning objective. Additionally, studies on teachers' voices of the emerging context of online learning platform over learner autonomy have not been well established. Therefore, the present study attempts to complement this line of research via a qualitative investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…As for students, it is useful to help them with learning fulfillment based on their preferences. It aligns with other studies (Almusharraf, 2020;Borg & Al-Busaidi, 2012;Ningsih & Yusuf, 2020;Yuzulia & Yusuf, 2019) have found. Similar to this research finding, Borg and Al-Busaidi (2012) reported that teachers participating in the study witness their autonomous students as individuals with several characteristics, such as having higher motivation, better commitment, more learning excitement, better focus, and bravery to take risks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As for students, it is useful to help them with learning fulfillment based on their preferences. It aligns with other studies (Almusharraf, 2020;Borg & Al-Busaidi, 2012;Ningsih & Yusuf, 2020;Yuzulia & Yusuf, 2019) have found. Similar to this research finding, Borg and Al-Busaidi (2012) reported that teachers participating in the study witness their autonomous students as individuals with several characteristics, such as having higher motivation, better commitment, more learning excitement, better focus, and bravery to take risks.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have investigated the attitudes of EFL teachers toward LA implementation in their teaching (Almusharraf, 2020;Lengkanawati, 2017;Ningsih & Yusuf, 2020;Yuzulia, 2020;Yuzulia & Yusuf, 2019), as well as the perspectives from students (Boonma & Swatevacharkul, 2020;Dalilan, 2021;Tuan, 2021). Lengkanawati (2017) found that the majority of the teachers participating in her study were eager to bring LA principles into teachinglearning practices, regardless of the challenges in its implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be inferred that learner autonomy in face-to-face learning environments is possible to promote despite the traditional trends in teaching, as stated by Ningsih and Yusuf (2021). Where teachers control the classroom, decisions regarding the lesson and the assessment remain in the hands of teachers.…”
Section: Literature Review Learner Autonomy In the Efl Fieldmentioning
confidence: 99%
“…To achieve this goal, young learners should read proficiently as well as engage and be motivated to read throughout elementary school (Martha et al, 2021). When teachers support young learners' need for autonomous reading activities, it allows them to opt for reading materials that they find interesting and grasp the value of reading text to achieve reading competency (Xie, 2020) and as a result, learners can exchange cultural views with speakers of the target culture and activating their prior knowledge (Ningsih & Yusuf, 2021).…”
Section: Introductionmentioning
confidence: 99%